Adenoids of patients with mucopolysaccharidoses demonstrate typical alterations. Issue 2 (February 2015) - Keilmann, Annerose; Läßig, Anne K.; Pollak-Hainz, Anja; Mann, Wolf J.; Beck, Michael; Hainz, Michael
Abstract Objective Tonsillar hypertrophy caused by the progressive accumulation of partially degraded glycosaminoglycans (GAGs) within the cells is a typical symptom in patients with mucopolysaccharidoses (MPS). We studied the tissue of adenoids and tonsils of patients suffering from MPS with special regard to characteristic morphological features serving as possible markers for diagnosis. Methods Adenoids of 87 patients and tonsils of 4 patients with MPS (2 patients with MPS I, 7 MPS II, 5 MPS IV and 10 MPS VI and 63 controls) and controls were examined. Examinations were repeated in a blinded manner by two pathologists. Results The key feature observed was a subepithelial "clearing" on scanning magnification, induced by perivascular accumulation of histiocytoid cell forms. Similar agglomerates could sometimes be found at the base of lymphoid follicles. In the blinded assessment a specificity of 92% (100% for adenoids) and a sensitivity of 100% were achieved. The inter-observer-consistency was 92% (100% for adenoids). In tonsillectomy specimens marked subepithelilal fibrosis can lead to a false-negative evaluation. Conclusions Qualified histological examination could be an option for early diagnosis of MPS.